Pendampingan Pengelolaan Website Kelurahan: Strategi Digitalisasi Pelayanan Masyarakat di Era Smart Village - USMAN, IRWAN; Hijrah, Muh.; Indi Rahayu , Putri; Hidayatullah , Muhammad; Budi Andy B , Afif; Arfah, Nur (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The development of information technology is a key driver of digital transformation in public services, including village governance. In the context of Smart Village development, digitalization of public services is a crucial strategy for increasing efficiency, transparency, and public participation. However, many village officials still face limitations in managing digital media, particularly websites, as the primary means of public information and services. This mentoring activity aims to increase the capacity of Baurung village officials in managing their websites effectively and sustainably. The mentoring is carried out through technical training and direct guidance covering content management, publication information, and the operation of online service features. The focus of the activity covers four main aspects: improving the quality of public services through easy access to online administration, transparency and accountability through open public information, community empowerment through increased digital literacy, and developing local potential through the promotion of micro, small, and medium enterprises' digital products and community activities. The results of the activity indicate an increase in the ability of village officials to manage websites and an increase in the effectiveness of digital-based public services. This activity is a strategic step in accelerating the implementation of Smart Villages in Baurung village by strengthening governance and capacity in the field of information technology